A selective inhibitor of the NLRP3 inflammasome as a potential therapeutic approach for neuroprotection in a transgenic mouse model of Huntington’s disease - Chen, Kai-Po; Hua, Kuo-Feng; Tsai, Fu-Ting; Lin, Ting-Yu; Cheng, Chih-Yuan; Yang, Ding-I.; Hsu, Hsien-Ta; Ju, Tz-Chuen (Journal of neuroinflammation, 2022)
Background Huntington’s disease (HD) is a neurodegenerative disorder caused by the expansion of the CAG repeat in the huntingtin ( HTT ) gene. When the number of CAG repeats exceeds 36, the translated expanded polyglutamine-containing HTT protein (mutant HTT [mHTT]) interferes with the normal functions of many cellular proteins and subsequently jeopardizes important cellular machineries in major types of brain cells, including neurons, astrocytes, and microglia. The NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasome, which comprises NLRP3, ASC, and caspase-1, is involved in the activation of IL-1β and IL-18 and has been implicated in various biological functions. Although the existence of the NLRP3 inflammasome in the brain has been documented, the roles of the NLRP3 inflammasome in HD remain largely uncharacterized. MCC950 is a highly selective and potent small-molecule inhibitor of NLRP3 that has been used for the treatment of several diseases such as Alzheimer’s disease. However, whether MCC950 is also beneficial in HD remains unknown. Therefore, we hypothesized that MCC950 exerts beneficial effects in a transgenic mouse model of HD. Methods To evaluate the effects of MCC950 in HD, we used the R6/2 (B6CBA-Tg[HDexon1]62Gpb/1J) transgenic mouse model of HD, which expresses exon 1 of the human HTT gene carrying 120 ± 5 CAG repeats. Male transgenic R6/2 mice were treated daily with MCC950 (10 mg/kg of body weight; oral administration) or water for 5 weeks from the age of 7 weeks. We examined neuronal density, neuroinflammation, and mHTT aggregation in the striatum of R6/2 mice vs. their wild-type littermates. We also evaluated the motor function, body weight, and lifespan of R6/2 mice. Results Systematic administration of MCC950 to R6/2 mice suppressed the NLRP3 inflammasome, decreased IL-1β and reactive oxygen species production, and reduced neuronal toxicity, as assessed based on increased neuronal density and upregulation of the NeuN and PSD-95 proteins. Most importantly, oral administration of MCC950 increased neuronal survival, reduced neuroinflammation, extended lifespan, and improved motor dysfunction in R6/2 mice. Conclusions Collectively, our findings indicate that MCC950 exerts beneficial effects in a transgenic mouse model of HD and has therapeutic potential for treatment of this devastating neurodegenerative disease.